Supercritical antisolvent precipitation of PHBV microparticles - Costa, M. S. (2007)
The micronization of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) from organic solutions using supercritical antisolvent (SAS) technique has been successfully achieved. SASexperiments were carried out at different operational conditions and microspheres with mean diameters ranging from 3 to 9 mwere obtained. The effect of CO2 and liquid flow, temperature and pressure on particle size and particle size distribution was evaluated. The microspheres were precipitated from a dichloromethane (DCM) solution. The best process conditions for this mixture were, according to our study, 40 ◦C, 100 bar, 1mLmin−1 liquid flow and 10 L min−1 carbon dioxide flow. Experiments with polymers containing different HV percentages were carried out. The powders obtained became more spherical as the HV content decreased.